Carbon nanosheet-based photo-thermal response film driver and preparation method and application thereof
By using carbon nanosheets and PET films synthesized by coconut hydration, combined with the design of the opposite drive response layer, the problems of poor response control accuracy and insufficient photothermal response sensitivity of existing soft driver materials are solved, achieving high accuracy and rapidity Responsive carbon nanosheet-based photothermal responsive film driver.
Patent Information
- Application Number
- CN202411634082.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
Smart Images

Figure CN119461339A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of soft robots, and in particular to a carbon nanosheet-based photothermal response thin film actuator and a preparation method and application thereof. Background Art
[0002] Various organisms in nature, such as octopus, jellyfish, Venus flytrap, mimosa, etc., can achieve precise directional movement and predation activities through stimulus-responsive actuation. Researchers have tried to develop artificial responsive soft actuators, including artificial muscles, intelligent actuators, soft robots, etc. There are two main technical limitations of existing soft actuator materials: First, the materials are mostly bulk structures with thickness sizes above the millimeter level, and the response control accuracy is poor; second, photothermal response materials have limitations. The photothermal conversion materials used in photothermal response actuators are mostly metal nanoparticles, inks, carbon black, etc. The photothermal response and recovery time are relatively long, and the sensitivity of the photothermal response needs to be further improved. New photothermal conversion materials need to be developed. Summary of the invention
[0003] In view of this, the present invention provides a carbon nanosheet-based photothermal response thin film actuator and its preparation method and application. The present invention uses coconut water synthesized carbon nanosheets as photothermal conversion materials, uses PET as a supporting layer film, and designs opposite driving response layers on both sides of the film to collaboratively achieve photothermal driving response behavior. The size of the prepared carbon nanosheet-based photothermal response thin film actuator can reach the micron level, with good control accuracy, strong sensitivity of photothermal response, and fast heating and cooling speed.
[0004] To achieve the above object, the present invention provides the following solutions:
[0005] One of the technical solutions of the present invention is a method for preparing a carbon nanosheet, comprising the following steps:
[0006] adding polyetherimide to coconut water to obtain a mixed solution;
[0007] The mixed solution is carbonized, and then water is added and freeze-dried to obtain the carbon nanosheets.
[0008] Furthermore, before adding polyetherimide to coconut water, the method further includes the steps of centrifuging and filtering the coconut water; the mass concentration of polyetherimide in the mixed solution is 0.2%-0.7%; the carbonization method is microwave heating carbonization, and the carbonization time is 1-10 minutes.
[0009] Furthermore, the molecular weight of the polyetherimide is 500-5000.
[0010] The second technical solution of the present invention is a carbon nanosheet prepared according to the above-mentioned method for preparing the carbon nanosheet.
[0011] The third technical solution of the present invention is a method for preparing a carbon nanosheet-based photothermal response thin film actuator, comprising the following steps:
[0012] UCST type monomer, crosslinking agent and photoinitiator are added into water and dissolved to obtain solution A;
[0013] Adding LCST type monomer, crosslinking agent and photoinitiator to the above carbon nanosheet solution to obtain solution B;
[0014] The solution A is coated on one side of the film and cured by ultraviolet light; the solution B is coated on the other side of the film and cured by ultraviolet light to obtain the carbon nanosheet-based photothermal responsive thin film actuator.
[0015] Furthermore, the concentration of the UCST monomer in the solution A is 2M-5M; in the process of preparing the solution A, the molar ratio of the UCST monomer, the crosslinking agent and the photoinitiator is 10:1:1, and the UV curing time is 0.5-5min.
[0016] Furthermore, the concentration of the LCST monomer in the solution B is 0.2M-2M; in the process of preparing the solution B, the molar ratio of the LCST monomer, the crosslinking agent and the photoinitiator is 10:1:1, and the UV curing time is 0.5-5min.
[0017] Furthermore, the concentration of carbon nanosheets in the solution of the carbon nanosheets is 200-500 mg / mL; the UCST-type monomer includes acrylylglycine amide; the LCST-type monomer includes N-isopropylacrylamide, acrylamide, 2-dimethylaminoethyl methacrylate, N-vinylcaprolactam, hydroxyethyl methacrylate, diethylacrylamide, and oligoethylene glycol methacrylate; the film is a polyethylene terephthalate film; the film is a polyethylene terephthalate film; the film thickness affects the rigidity and driving performance of the material, and the film thickness is 10-100 microns, and preferably the film thickness is 12.5 microns.
[0018] Furthermore, in the step of coating the solution A on one side of the film and curing it, the coating method is spin coating, the curing method is ultraviolet light curing, and the number of coating layers is 2 to 9 layers;
[0019] In the step of coating the solution B on the other side of the film and curing it, the coating method is spin coating and the curing method is ultraviolet light curing; the total number of layers coated with the solution A and the solution B is 10 layers.
[0020] A fourth technical solution of the present invention is a carbon nanosheet-based photothermal responsive thin film actuator prepared according to the above-mentioned method for preparing the carbon nanosheet-based photothermal responsive thin film actuator.
[0021] A fifth technical solution of the present invention is the use of the above-mentioned carbon nanosheet-based photothermal response thin film actuator in the preparation of deformable materials or devices under near-infrared light stimulation conditions.
[0022] The present invention discloses the following technical effects:
[0023] 1) The carbon nanosheets prepared from coconut water as a raw material in the present invention are used as photothermal conversion materials, which have the advantage of high sensitivity of photothermal response.
[0024] 2) The preparation method of the carbon nanosheet-based photothermal responsive thin film actuator of the present invention has a simple preparation process, mild and controllable reaction conditions, and is easy to promote.
[0025] 3) The size of the carbon nanosheet-based photothermal response thin film actuator prepared by the method of the present invention can reach the micron level, the driving process can be accurately controlled, and fine components can be prepared. The photothermal response is highly sensitive, the heating and cooling speeds are fast, and the photothermal response and recovery time are short and repeatable. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 TEM observation images and atomic force test results of the carbon nanosheets prepared in Example 1; wherein (a) is the TEM observation image, and (b) is the atomic force test result.
[0028] Figure 2 It is a driving schematic diagram of the carbon nanosheet-based photothermal response thin film actuator (hydrogel thin film actuator) of the present invention.
[0029] Figure 3 The response of an actuator with 10 PNIPAM layers and different UV curing times under near-infrared light: (a) UV curing time 1 min; (b) UV curing time 2 min; (c) UV curing time 3 min.
[0030] Figure 4 This is a microstructure diagram of the hydrogel film actuator prepared in Example 2.
[0031] Figure 5 The response and recovery of the hydrogel film actuator prepared in Example 2.
[0032] Figure 6The response driving and recovery data of the hydrogel film actuator prepared in Example 2. DETAILED DESCRIPTION
[0033] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0034] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0035] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0036] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0037] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0038] The "room temperature" described in the present invention, unless otherwise specified, refers to 15-30°C.
[0039] A first aspect of the present invention provides a method for preparing a carbon nanosheet, comprising the following steps:
[0040] adding polyetherimide to coconut water to obtain a mixed solution;
[0041] The mixed solution is carbonized, and then water is added and freeze-dried to obtain the carbon nanosheets.
[0042] In a preferred embodiment of the present invention, before adding polyetherimide to coconut water, the method further includes the steps of centrifuging and filtering the coconut water; the mass concentration of polyetherimide in the mixed solution is 0.2%-0.7%; and the carbonization method is microwave heating carbonization.
[0043] The power of the microwave heating is 700W, and the carbonization time is 1-10min. If the microwave heating time is too long or too short, the effect of photothermal conversion will be affected, and the optimal time is 4min.
[0044] In a preferred embodiment of the present invention, the molecular weight of the polyetherimide is 500-5000.
[0045] In the present invention, when the mass concentration of polyetherimide in the mixed solution is too high, the carbonization degree is too high and the material is severely gelatinized. When the mass concentration is too low, the photothermal conversion effect of the material is poor and the driving performance of the driver finally prepared is poor.
[0046] In the present invention, when the molecular weight of polyetherimide is too high, the carbonization degree is too high and the material is severely gelatinized. When the molecular weight is too low, the N source of the carbon nanosheet introduces few functional groups, the photothermal conversion effect of the material is poor, and the driving performance of the final prepared actuator is poor.
[0047] A second aspect of the present invention provides a carbon nanosheet prepared according to the above-mentioned method for preparing the carbon nanosheet.
[0048] A third aspect of the present invention provides a method for preparing a carbon nanosheet-based photothermal responsive thin film actuator, comprising the following steps:
[0049] UCST type monomer, crosslinking agent and photoinitiator are added into water and dissolved to obtain solution A;
[0050] Adding LCST type monomer, crosslinking agent and photoinitiator to the above carbon nanosheet solution to obtain solution B;
[0051] The solution A is coated on one side of the film and cured; the solution B is coated on the other side of the film and cured to obtain the carbon nanosheet-based photothermal responsive thin film actuator.
[0052] In a preferred embodiment of the present invention, the concentration of the UCST monomer in the solution A is 2M-5M; during the preparation of the solution A, the molar ratio of the UCST monomer, the crosslinking agent and the photoinitiator is 10:1:1.
[0053] In a preferred embodiment of the present invention, the concentration of the LCST type monomer in the solution B is 0.2M-2M; and during the preparation of the solution B, the molar ratio of the LCST type monomer, the crosslinking agent and the photoinitiator is 10:1:1.
[0054] In a preferred embodiment of the present invention, the concentration of the carbon nanosheets in the solution of the carbon nanosheets is 200-500 mg / mL; the solvent in the solution of the carbon nanosheets is deionized water;
[0055] In the solution of carbon nanosheets, as the concentration of carbon nanosheets increases, the photothermal conversion performance is enhanced, but the viscosity of the solution increases, and the coating process cannot achieve uniform coating when the viscosity is high. Therefore, the preferred concentration of carbon nanosheets in the present invention is 200-500 mg / mL.
[0056] The UCST type monomer is acryloyl glycinamide;
[0057] The LCST type monomer is N-isopropylacrylamide;
[0058] The present invention also attempts to use other commonly used monomers in the art, such as acrylamide (AAM), 2-dimethylaminoethyl methacrylate (DMAM), N-vinyl caprolactam (NVCL), hydroxyethyl methacrylate (HEMA), diethylacrylamide (DEAA) and oligoethylene glycol methacrylate (OEGMA) as LCST-type monomers. The results show that when the UCST-type monomer is acrylylglycinamide and the LCST-type monomer is N-isopropylacrylamide, the prepared carbon nanosheet-based photothermal responsive thin film actuator has the best responsiveness.
[0059] The crosslinking agents used in the preparation of the solution A and the solution B are both N,N'-methylenebisacrylamide, and the photoinitiators are both Ir.2959.
[0060] In a preferred embodiment of the present invention, in the step of coating the solution A on one side of the film and curing it, the coating method is spin coating, the curing method is ultraviolet light curing, and the number of coating layers is 2 to 9 layers.
[0061] In the step of coating the solution B on the other side of the film and curing it, the coating method is spin coating and the curing method is ultraviolet light curing; the total number of layers coated with the solution A and the solution B is 10 layers.
[0062] A fourth aspect of the present invention provides a carbon nanosheet-based photothermal responsive thin film actuator prepared according to the above-mentioned method for preparing the carbon nanosheet-based photothermal responsive thin film actuator.
[0063] Unless otherwise specified, the raw materials used in the embodiments of the present invention can be obtained through commercial sources.
[0064] The coconut water used in the embodiment of the present invention is the coconut water of fresh Wenchang tender coconut.
[0065] The molecular weight of the polyetherimide (PEI) used in the embodiment of the present invention is 2000.
[0066] The driving schematic diagram of the carbon nanosheet-based photothermal response film actuator (hydrogel film actuator) of the present invention is as follows: Figure 2 As shown; in the figure, LCST represents the lower critical solution temperature, and UCST represents the higher critical solution temperature.
[0067] A fifth aspect of the present invention provides the use of the above-mentioned carbon nanosheet-based photothermal response thin film actuator in the preparation of materials or devices that can deform under near-infrared light stimulation conditions.
[0068] Example 1 Preparation of carbon nanosheets
[0069] Early exploratory experiments
[0070] PEI molecular weight regulation: 200, 2000, and 20000 molecular weight PEI were used for carbonization. When the molecular weight was 20000, the size of the nanomaterial synthesis was too large, and the carbonization process was prone to gelatinization. When the molecular weight was 200, the size of the nanomaterial synthesis was too small, and the photothermal conversion effect was poor. When the molecular weight was 2000, the size of the carbon nanosheet was appropriate, and the photothermal conversion performance was good.
[0071] The microwave carbonization time was adjusted to 1.0min, 2.0min, 3.0min, 4.0min, 5.0min, 6.0min, 7.0min, 8.0min, 9.0min and 10.0min respectively. When the time exceeded 6min, the carbonization process was prone to excessive carbonization into carbon cores. When the carbonization time was less than 2min, uniform nanoparticles could not be formed. Therefore, the carbonization time could be adjusted within the range of 2-6min, and the optimal carbonization time was 4min.
[0072] Step 1, centrifuging the coconut water (rotating speed 12000r / min, centrifuging for 20 minutes), and filtering (filter membrane pore size is 22 microns) to obtain a clear liquid without impurities.
[0073] Step 2, adding polyetherimide (PEI) to the above liquid so that 1 g of PEI is contained in every 200 mL of the liquid to obtain a mixed solution.
[0074] Step 3, take 10mL of the above mixed solution and place it in a 250mL beaker, put it into a microwave oven for medium-low heat microwave heating carbonization (power 700w), and the carbonization heating time is 4 minutes; then use 1.5mL of pure water to repeatedly collect the residual material in the beaker and cool it to room temperature to obtain a carbon nanosheet solution, and freeze dry it in a freeze dryer to obtain carbon nanosheets (solid), marked as PEI-CCS.
[0075] The TEM observation image and atomic force test results of the carbon nanosheets prepared in this example are as follows: Figure 1As shown, the diameter of carbon nanosheets was tested by field emission transmission electron microscopy, and the morphology and structure of PEI-CCS were characterized by atomic force microscopy. Figure 1 It can be seen that the average diameter of the carbon material prepared by microwave heating for 4 minutes is 200-300 nm, and the thickness of the carbon material is 1-5 nm. It can be judged that PEI-CCS is a carbon nano-flake material with a high middle and low surroundings.
[0076] Example 2 Preparation of hydrogel film
[0077] Preliminary exploratory experiments:
[0078] The UV curing time can be adjusted to 0.5-5min. If the curing time is too long, the dry weight of the material will increase, and overheating will occur during the driving process. If the curing time is too short, the cross-linking degree of the polymer network will be weak, and the material driving response will be slow. The optimal curing time is 1min-3min, which can be adjusted according to the monomer concentration of the LCST and UCST layers.
[0079] like Figure 3 As shown in the figure, when the UV curing time reaches 3 minutes, the material overheats and ignites, and the driving effect cannot be guaranteed. Therefore, there is an optimal time for UV curing, which can be adjusted for different concentrations of monomers.
[0080] The number of times layer A and layer B are spin-coated affects the overall thickness of the material. When the thickness of the polyethylene terephthalate film is 12.5 μm, the total number of layers is controlled to be 2-14 layers and it is found that the driving effect is best when the total number of layers A+B=10 layers.
[0081] Step 1: dissolve monomer acryloyl glycinamide (NAGA), crosslinker N,N'-methylenebisacrylamide (MBAA), and photoinitiator Ir.2959 in pure water in sequence to obtain solution A; the monomer concentration in solution A is 4M, and the molar ratio of the monomer to the crosslinker and initiator is 10:1:1.
[0082] Step 2: using 350 mg / mL carbon nanosheet solution (using the carbon nanosheet prepared in Example 1, the solvent of the carbon nanosheet solution is deionized water) to sequentially dissolve monomer N-isopropylacrylamide (NIPAM), crosslinker MBAA, and photoinitiator Ir.2959 to obtain solution B; the monomer concentration in solution B is 1 M. And the molar ratio of the monomer to the crosslinker and initiator is 10:1:1.
[0083] Step 3, take a rectangular polyethylene terephthalate film (PET film, thickness is 12.5 microns) with a side length of 4 cm, and fix it on a rectangular glass sheet with a side length of 6 cm with waterproof tape. The tape is attached all around the film and fixed firmly, leaving a rectangular film with a side length of 3 cm.
[0084] Step 4, take 200 μl of solution A, drop it on the PET film fixed in step 3, and spin coat it with a spin coater, with the speed set to 1000 r / min and the time set to 60 s. After the spin coating is completed, use ultraviolet light with a wavelength of 365 nm to cure for 1 minute; repeat the above spin coating-curing steps 3 times to prepare the PNAGA hydrogel layer.
[0085] Step 5. Gently peel off the tape and PET film from the glass, and try to avoid bending or wrinkling the film. Cut off the excess tape around the film with a blade, turn the PET film over, and use tape to firmly stick the four sides of the PET film to the glass, revealing a rectangular film with a side length of 3 cm.
[0086] Step 6, take 200 microliters of solution B, drop it on the PET film, and spin coat it with a spin coater. The speed is set to 1000r / min and the time is set to 60s. After the spin coating is completed, it is cured with ultraviolet light with a wavelength of 365nm for 2 minutes; repeat the above steps 7 times to prepare the PNIPAM layer, and the number of repetitions of step 4 and step 6 is a total of 10 times to obtain a carbon nanosheet-based photothermal responsive thin film actuator (hydrogel thin film actuator).
[0087] The microstructure of the hydrogel film actuator prepared in this embodiment is shown in FIG. Figure 4 As shown. Figure 4 It can be seen that the thickness of the middle layer is about 12.5μm, which matches the thickness of the commercially available PET film. The thinner upper layer is a three-layer spin-coated PNAGA hydrogel layer with a thickness of about 5.6μm. The thicker layer is a seven-layer spin-coated PNIPAM layer with a thickness of about 20μm. The overall thickness of the actuator is about 38μm.
[0088] The time required for the hydrogel film actuator prepared in this embodiment to respond 180 degrees, the recovery time, and the number of repetitions were tested, and the specific test method is as follows: the hydrogel film actuator is irradiated with a near-infrared laser, the power of the laser is set to 5000mW, the wavelength of the near-infrared light is 808nm, and the distance between the light source and the hydrogel film actuator is controlled to be 3cm. Under the irradiation of the near-infrared laser, an optical camera is used to record the response degree and response rate of the hydrogel film actuator after being stimulated by near-infrared light. Subsequently, the near-infrared light source is removed, and the optical camera is continued to be used to record the recovery behavior of the hydrogel film actuator after the light source is removed. The ambient temperature is 25°C, and the ambient humidity is 73±3%RH. The results are as follows. Figure 5 shown.
[0089] Figure 5 It shows that the hydrogel film actuator prepared in this embodiment takes 4 seconds to respond 180 degrees, takes 30 seconds to recover, and can be repeated 120 times. Figure 6As shown, after 120 repetitions, the driver response performance is basically maintained.
[0090] In order to further demonstrate the beneficial effects of the present invention and to better understand the present invention, the following comparative examples are used to further illustrate the technical features disclosed in the present invention, but they should not be construed as limiting the present invention. Other improvements made by those skilled in the art based on the above invention content without inventive work are also considered to fall within the scope of protection of the present invention.
[0091] The present invention prepares a photothermal conversion material by regulating the number of UCST and LCST layers, controls the number of UCST gel layers and LCST gel layers by repeating steps 4 and 6, and prepares photothermal responsive thin film actuators with layer ratios of 1+9, 2+8, 3+7, 4+6, and 5+5, respectively. The photothermal response performance thereof is shown in Table 1, wherein when the UCST layer is 3 and the LCST layer is 7, the photothermal response time is the shortest and the photothermal response effect is the most sensitive under standard conditions of bending 90° or bending 180°.
[0092] Table 1 Comparison of response performance of photothermal conversion materials with different USCT and LCST layers
[0093]
[0094]
[0095] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing carbon nanosheets, characterized in that: The following steps are involved: adding polyetherimide to coconut water to obtain a mixed solution; The mixed solution is carbonized, and then water is added and freeze-dried to obtain the carbon nanosheets.
2. The method for preparing carbon nanosheets according to claim 1, characterized in that: Before adding polyetherimide to coconut water, the method further includes the steps of centrifuging and filtering the coconut water; the mass concentration of polyetherimide in the mixed solution is 0.2%-0.7%; the carbonization method is microwave heating carbonization, and the carbonization time is 1-10 minutes.
3. The method for preparing carbon nanosheets according to claim 1, characterized in that: The molecular weight of the polyetherimide is 500-5000.
4. A carbon nanosheet prepared by the method according to any one of claims 1 to 3.
5. A method for preparing a carbon nanosheet-based photothermal responsive thin film actuator, characterized in that: The following steps are involved: UCST type monomer, crosslinking agent and photoinitiator are added into water and dissolved to obtain solution A; Adding LCST type monomer, crosslinking agent and photoinitiator to the solution of carbon nanosheets as claimed in claim 4 to obtain solution B; The solution A is coated on one side of the film and cured by ultraviolet light; The solution B is coated on the other side of the film and UV-cured to obtain the carbon nanosheet-based photothermal responsive thin film actuator.
6. The method for preparing the carbon nanosheet-based photothermal responsive thin film actuator according to claim 5, characterized in that: The concentration of the UCST monomer in the solution A is 2M-5M; during the preparation of the solution A, the molar ratio of the UCST monomer, the crosslinker and the photoinitiator is 10:1:1, and the UV curing time is 0.5-5min; The concentration of the LCST monomer in the solution B is 0.2M-2M; during the preparation of the solution B, the molar ratio of the LCST monomer, the crosslinking agent and the photoinitiator is 10:1:1, and the UV curing time is 0.5-5min.
7. The method for preparing the carbon nanosheet-based photothermal responsive thin film actuator according to claim 5, characterized in that: The concentration of carbon nanosheets in the carbon nanosheet solution is 200-500 mg / mL; the UCST type monomer includes acrylylglycinamide; the LCST type monomer includes N-isopropylacrylamide, acrylamide, 2-dimethylaminoethyl methacrylate, N-vinylcaprolactam, hydroxyethyl methacrylate, diethylacrylamide, and oligoethylene glycol methacrylate; the film is a polyethylene terephthalate film; and the thickness of the film is 10-100 microns.
8. The method for preparing the carbon nanosheet-based photothermal responsive thin film actuator according to claim 5, characterized in that: The coating method is spin coating, the curing method is ultraviolet light curing, the coating layers of solution A are 2 to 9 layers; the total coating layers of solution A and solution B are 10 layers.
9. A carbon nanosheet-based photothermal responsive thin film actuator prepared by the method according to any one of claims 5 to 8.
10. Use of the carbon nanosheet-based photothermal responsive thin film actuator as claimed in claim 9 in preparing materials or devices that deform under near-infrared light stimulation conditions.
Citation Information
Cited By
Low-irradiation photo-thermal soft driver and preparation method and application thereof
CN121625094A
Low irradiation light-heat soft driver and preparation method and application thereof
CN121625094B